Interrelationship between Skeletal and Visceral Metastases in Invasive Ductal Carcinoma of Breast- Observational Study at INMAS, Mitford, Dhaka - Sharmin, Samira; Naznin, Afroza; Rahman, Hosne Ara; Billah, Syed Muhammad Baqui; Yasmin, Farida; Salekin, Md Simoon; Hossain, Jamiul; Uddin, Md Monir; Hossian, Arshad; Tasnim, Humayra; et al. (Bangladesh Journal of Nuclear Medicine, 2023)
Background: Invasive Ductal Carcinoma (IDC) is the most common of all diagnosed breast cancers, and it frequently presents with metastatic spread to the bone as well as other viscera. Bone scintigraphy is the primary tool for detecting bone metastases, while different imaging modalities can be useful in detecting visceral metastases. The purpose of this study was to determine the relationship between skeletal and visceral metastases in female patients with IDC referred to INMAS, Mitford, for bone scintigraphy. Patients and Methods: This observational study was conducted at the Institute of Nuclear Medicine and Allied Sciences (INMAS), Mitford, Dhaka, from July 2020 to July 2021. Bone scintigraphy was done with a Siemens dual-head gamma camera after an intravenous injection of 20 mCi of 99mTc-MDP. Both anterior and posterior views were obtained, with additional SPECT images when needed. Images were interpreted and analysed by Nuclear Medicine (NM) physicians of this institute. Data about visceral metastases were collected from patients’ record files. Results: The patients were divided into two groups based on the presence of visceral metastases. Group-A had 95 patients with no known metastases to the viscera, and in Group-B, there were 50 patients who had documented visceral metastases. The majority of the patients in the first group (53.7%) showed no bone metastasis, while a small portion (5.3%) revealed a solitary skeletal metastatic lesion and the rest (41.1%) presented with multiple skeletal metastases. Sixty-six percent of patients in Group B had solitary visceral metastases, with the remaining 34% having metastases to multiple viscera. All the patients in this group were affected at various levels by secondary skeletal deposits. Conclusion: The findings of the study revealed that the presentation of visceral metastases was related to the extent and severity of bone metastases in patients with carcinoma of the breast. Bangladesh J. Nuclear Med. 25(2): 117-120, 2022